(3JbQjX efXhe Ydi cJGH JjLGf GdYfhGf Ydi eKGd YfhGf GdTQas - (3YHO GdQMef Hf Ydj GdOjfs ((3eMeO Cejf Hf YeQ Hf eMeO GdOfai GdCfUGQi s)
(3ChdgG (B:s
(3CMeO ef HhGaQ GdfYe Ydi ef ENJGQ dEQTGO GdCee hNU efgG HYdi GdQJH hZGjI GdeLO hCQbi efUH s
(3BNQgG (B:s
(3aGdMeO NJGe fXei Ke Ydi PGJ GdfHi GdCei CRci GdUdGI hGdSdGe GdOGFe hGdBd hGdUMH Phi GdecGQe eG ZQOJ SGLYI Ydi ajf heG SMJ acQI Pi aVd Off JeJ HMeO Gddg hYhfg hMSf Jhajbg hGdMeO ddg hMOg hUdi Gddg Ydi ef dGfHi HYOg Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3fSNI ecQQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs